P12.05 Pulmonary embolism in neuroncological patients: Monoistitutional experience. (9th September 2021) - Gaviani, P; Simonetti, G; Redaelli, V; Botturi, A; Corsini, E; Silvani, A
Abstract: BACKGROUND: Venous thromboembolism (VTE) is a frequent and potentially fatal event in cancer patients. Patients with brain tumors in particular have one of the highest risk of developing VTE among cancer patients (25–39%), contributing significantly to mortality and morbidity. VTE is particularly high in the postoperative period, with almost half of the events occurring at that time, but it also persists in the first 12 months, with a risk ranging between 7–28%. Despite the high incidence of VTE in patients with brain tumors, to date there are no sufficient data to predict teh real risk or to lead to a standardized approach in the management of these patients. We conducted a retrospective analysis to assess the prevalence of pulmonary embolism complication in patients with brain tumors treated by our Institution in the last 3 years. MATERIAL AND METHODS: Clinical data, treatment modalities, and patients outcome were analyzed and described. In particular, In particular, the dosages of D-dimer performed in the clinical suspicion of thromboembolic complication were reviewed, and the data of patients with pulmonary embolism confirmed by chest CT scan were recorded. RESULTS: Overall 372 patients were treated at our Institute in the last 3 years for brain tumors. 14 patients (3.7%) 9 males and 5 females, with a median age of 62 years and a median KPS of 80, affected by glioblastoma (69%), cerebral lymphoma (23%) and low-grade gliomas (8%) had pulmonary embolism during the course of treatment. None of the 14 patients was on prophylactic anticoagulant treatment. One patient developed the embolic event during radio and chemotherapy concomitant treatment, 5 patients during chemotherapy only (2 with PCV scheme and 3 with fotemustine scheme), 2 patients with primary nervous system lymphoma during methotrexate infusion. Six patients were not receiving any chemotehrapy treatment at the onset of pulmonary embolism. At the time of pulmonary embolism diagnosis, more than half of the patients had clinical signs suggestive of deep venous thrombosis, confirmed by echocolor Doppler, 10/14 patients were treated with high-dose enoxaparin, the others with fondaparinux and calcium nadroparin. CONCLUSION: Despite the high incidence of VTE in patients with brain tumors, there is currently no gold standard in the prevention and treatment of this complication. In fact, many questions are still open, for example the efficacy of low molecular weight heparins vs oral anticoagulants as a prophylactic treatment, the timing of onset and the real risk of bleeding. Future prospective studies should be designed to identify parameters for optimize stratification of thrombotic / haemorrhagic risk in this group of patients. This could allow patients at high risk to undergo more aggressive prophylactic therapy or closer clinical-instrumental surveillance, without incurring the opposite risk of bleeding.